Kepentingan Nasional Arab Saudi Dalam Akuisisi Newcastle United FC Melalui Public Investment Fund Pada Tahun 2021 - Muhammad Ghaits Falah; Muchammad Yustian Yusa (Sriwijaya Journal of International Relations, 2023)
This research aims to further examine the national interest that Saudi Arabia seeks to achieve in the acquisition of Newcastle United FC. Researcher uses the concept of National Interest by Donald E. Nuechterlein as theoretical framework that has four dimensions consisting of: Economic Interests, World Order Interests, Defence Interests, and Ideological Interests. This study shows that the acquisition of Newcastle United by Saudi Arabia only fulfils 1 of the 4 national interests of Saudi Arabia, which is world order interest. Furthermore, this acquisition is being used by Saudi Arabia as a means of sportswashing to clean up the country's negative image through sports.